An assessment of the process and institutional requirements of monitoring and evaluation systems in government : a case study of the KwaZulu-Natal Department of Arts and Culture - Mtshali, Jephrey Mfuniseni (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPA)--Stellenbosch University, 2014.